D-arginine Enhances the Effect of Alpha-Amylase on Disassembling Actinomyces viscosus Biofilm - Li, Baosheng; Cai, Qing; Wang, Zixuan; Qiao, Shuwei; Ou, Yanzhen; Ma, Rui; Luo, Chuanfu; Meng, Weiyan (Frontiers in Bioengineering and Biotechnology, 2022)
Peri-implantitis is the leading cause of dental implant failure, initially raised by biofilm accumulation on the implant surface. During the development of biofilm, Actinomyces viscosus (A. viscosus) plays a pivotal role in initial attachment as well as the bacterial coaggregation of multispecies pathogens. Hence, eliminating the A. viscosus-associated biofilm is fundamental for the regeneration of the bone resorption around implants. Whereas clinical evidence indicated that antimicrobials and debridement did not show significant effects on the decontamination of biofilm on the implant surface. In this study, alpha-amylase was investigated for its effects on disassembling A. viscosus biofilm. Then, in order to substantially disperse biofilm under biosafety concentration, D-arginine was employed to appraise its enhancing effects on alpha-amylase. In addition, molecular dynamics simulations and molecular docking were conducted to elucidate the mechanism of D-arginine enhancing alpha-amylase. 0.1%-0.5% alpha-amylase showed significant effects on disassembling A. viscosus biofilm, with definite cytotoxicity toward MC3T3-E1 cells meanwhile. Intriguingly, 8 mM D-arginine drastically enhanced the eradication of A. viscosus biofilm biomass by 0.01% alpha-amylase with biosafety in 30 min. The exopolysaccharides of biofilm were also thoroughly hydrolyzed by 0.01% alpha-amylase with 8 mM D-arginine. The biofilm thickness and integrity were disrupted, and the exopolysaccharides among the extracellular matrix were elusive. Molecular dynamics simulations showed that with the hydrogen bonding of D-arginine to the catalytic triad and calcium-binding regions of alpha-amylase, the atom fluctuation of the structure was attenuated. The distances between catalytic triad were shortened, and the calcium-binding regions became more stable. Molecular docking scores revealed that D-arginine facilitated the maltotetraose binding process of alpha-amylase. In conclusion, these results demonstrate that D-arginine enhances the disassembly effects of alpha-amylase on A. viscosus biofilm through potentiating the catalytic triad and stabilizing the calcium-binding regions, thus providing a novel strategy for the decontamination of biofilm contaminated implant surface.